Training strategy and its impact on the performance of employees in Kuwaiti industrial companies - Marafi, Fatima Abdulwahid (Journal of Economic, Administrative and Legal Sciences, 2023)
The aim of the study was to identify the impact of the training strategy on the performance of workers in industrial companies in the State of Kuwait, and it also aimed to know the reality of the training strategy in Kuwaiti industrial companies, and aimed to know the degree of performance of workers in Kuwaiti industrial companies and to achieve the objectives of the study, the researcher relied on the descriptive correlational approach, and the sample was chosen randomly, which amounted to (194) employees, and the study tool was developed, which is a (questionnaire) that relied on its development through the scale adopted in the study of Saeed (2019) and the scale Adopted in the study of Abu Al-Asis (2022) in order to measure the training strategy and its impact on the performance of workers in industrial companies in the State of Kuwait, where it consisted of (20) items, distributed on two axes, and the researcher verified its honesty and stability, and the study came out with a set of results, the most important of which were, There is a significant positive impact of the training strategy on the performance of workers in Kuwaiti industrial companies, and it was found that the reality of the training strategy in Kuwaiti industrial companies from the point of view of employees was large, and that the degree of performance of workers in Kuwaiti industrial companies from the point of view of employees was large, and based on the results of the study, the most important recommendations were on the Kuwaiti Industrial Company to provide various training programs throughout the year, Kuwaiti companies should continue to work to identify the training needs of workers through Periodic evaluation of performance.
Keywords: Training strategy; employee performance; industrial companies; Kuwait